2. Supervisi Bersama Dengan Teknik Lomba Penilaian Administrasi Meningkatkan Kualitas Madrasah Ibtidaiyah Binaan Kecamatan Tanah merah Bangkalan - Usman, M. (JURNAL WAHANA PENDIDIKAN DASAR, 2017)
Supervisory Madrasah is functional official who serves as technical executor in carrying out surveillance of Education with the main task to assess and foster education at a Madrasah, given both public and private that is its responsibility, as stipulated in the decree Mendiknas number 020 / U / 1998 and SK Menpan number 091 / Kep / M.PAN / 10/2001 and SK Mendiknas number 097 / U / 2002.                In performing its duties Madrasah Supervisors have the authority to select and define working methods in order to achieve optimum results in accordance with the code of professional conduct. Regulation of the Minister of National Education of the Republic of Indonesia No. 19 of 2007 on the management standards by educational units include 1. Planning program. 2. Implementation of the work plan. 3. Monitoring and evaluation. 4. Leadership Madrasah / madrasah. 5. The management information system. 6. Special Rate.                The term supervision comes from two words, "super" and "vision". In webstr's new world dictiori term super mean "higher in rank or position than, superior to (superintendent), a greater or better than other" (1991: 1343) while the word vision means "the ability to perceive something not actuality visible, as a trough acutness mental or keen foresight (1991: 1492)                This research is an action research (action research) that aims to improve the administrative management of Madrasahs through supervision along with race engineering administration. Actions to be carried out assessing the completeness of the administration. This type of research is the kind of action that have emancipatory. Emancipatory kind was considered the most appropriate for this study was conducted to solve the problems on their own researchers working area based on everyday experience.                From the first cycle to the second cycle and observations indicate mental readiness Madrasah head completeness administrrasi 86.36% 70.21% and 89.36% holder staek support assessment of the team is not good supervesor showed 3.68% 1.23% quite good 41, 18% very good 46.32%. It can be concluded that supervision along with race administration Madrasah Madrasah improve the quality acceptable.